An investigation of the interaction of class attendance, tutorials, mentor sessions, video presentations and external tutoring, and the effect thereof on student performance - Ontong, J.M.; Bruwer, A.; Dreyer, J.A. (South African Journal of Higher Education, 2020)
The need to improve the systematic failures of higher education has led to various studies that promote the implementation of certain types of teaching interventions with the aim of increasing student performance. This study investigates the effects of these interventions on student performance in a multiple-intervention environment by developing an attendance construct proxy, as well as an alternative to the class attendance intervention construct proxy. The benefits of these interventions were analysed to determine whether certain interventions have a more significant impact on student performance than others in the context of increasing student performance. Using a survey approach to determine the record of participation in the interventions by the students, the findings of participation were analysed using the academic records of the students to identify the effect. The results suggest that increased levels of attending classes, which include traditional and additional face-to-face sessions, have a significant positive effect on student performance. When analysing the additional face-to-face sessions, specifically the further class attendance of tutorial classes where students are given the opportunity to work on their own or in groups and only request assistance where needed, the greatest significant positive effect on student performance was observed. The findings further suggest that certain interventions – often seen as alternatives to class attendance, such as attending mentor sessions, external tutoring, and watching videos of beginners’ classes – do not necessarily have a positive significant effect on student performance. Interestingly, the perceptions of students are consistent with the findings of the study, with the majority of students not recommending the use of external tutoring services. The findings of the study therefore provide insightful value to the design of modules at higher education institutions, aiding in identifying and responding to which interventions would have a significant impact on student performance.